2011
DOI: 10.1260/1747-9541.6.2.301
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality Traits and Coachability in NCAA Divisions I and II Female Softball Athletes

Abstract: Coaches at all levels desire coachable athletes whose personalities are a good fit for their teams. Coachability is a complex construct that is not well understood in the sport science literature, but appears to be demonstrated through several behaviors. Costa and McCrae's Five Factor Model framework proposes that personality traits are inherent and predispose a person to behave in relatively stable ways. This study used survey methodology to investigate relationships between head college coaches' (n = 36) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…These findings compliment recent research in amateur coaches that found coaches perceive athletes as easier to instruct and mentor if they are highly agreeable and/or 22 emotionally stable (Favor, 2011). The contribution of personality to relationship commitment and relatedness is apparent both inside and outside competitive sport (Jackson et al, 2011).…”
Section: Social Interactions and Group Dynamicssupporting
confidence: 88%
“…These findings compliment recent research in amateur coaches that found coaches perceive athletes as easier to instruct and mentor if they are highly agreeable and/or 22 emotionally stable (Favor, 2011). The contribution of personality to relationship commitment and relatedness is apparent both inside and outside competitive sport (Jackson et al, 2011).…”
Section: Social Interactions and Group Dynamicssupporting
confidence: 88%
“…The athletes' personal characteristics and level of development refer to the variables pertaining to athletes' current stage of learning, personal background, and other characteristics that influence interactions with their coach (Côté et al, 1995). Many expert intercollegiate coaches view the athletes' personal characteristics as an important, sometimes even stronger predictor, of the athletes' success than performance excellence in their previous level of athletics (Favor, 2011;Giacobbi, Roper, Whitney, & Butryn, 2002). In fact, Giacobbi and colleagues found that college coaches viewed athletes' psychological qualities including commitment and responsibility as important predictors in making successful transitions from high school to college athletics.…”
Section: Coaching Modelmentioning
confidence: 99%
“…Coachability is a complex construct often described as athletes' receptivity towards coach feedback and instructions (Favor, 2011).…”
Section: Literature Review 16mentioning
confidence: 99%
See 2 more Smart Citations